The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1991
DOI: 10.1126/science.1840704
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a Zinc Finger Protein that Inhibits IL-2 Gene Expression

Abstract: Transient activation of the interleukin-2 (IL-2) gene after antigen recognition by T lymphocytes is crucial for subsequent T cell proliferation and differentiation. Several IL-2 gene regulatory elements and binding factors necessary for activation of the IL-2 gene have been defined. However, little is known about negative regulation of IL-2 expression, which is likely to be important in the rapid shut-off of IL-2 transcription. A nucleotide sequence element (NRE-A) that negatively regulates IL-2 expression has… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
97
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 180 publications
(100 citation statements)
references
References 33 publications
2
97
0
Order By: Relevance
“…These results demonstrated that the optimal consensus binding sequence of AREB6#2 is C/TACCTG/TT. This matches the inverted sequence of Nil-2-a binding site, NRE-A(GA-CAGGTAAA), which was identified as the negative regulatory element located upstream of the IL-2 gene promoter (Williams et al, 1991). To determine the optimal binding sequences or detailed binding sequence requirements for AREB6#1 and AREB6#5 in comparison with AREB6#2, we performed gel mobility shift assays with the same set of competitors as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…These results demonstrated that the optimal consensus binding sequence of AREB6#2 is C/TACCTG/TT. This matches the inverted sequence of Nil-2-a binding site, NRE-A(GA-CAGGTAAA), which was identified as the negative regulatory element located upstream of the IL-2 gene promoter (Williams et al, 1991). To determine the optimal binding sequences or detailed binding sequence requirements for AREB6#1 and AREB6#5 in comparison with AREB6#2, we performed gel mobility shift assays with the same set of competitors as shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As the second set, we performed transient cotransfection into Jurkat cells using the naturally occurring IL-2 promoter, which contains the Nil-2-a binding site, NRE, at -110 to -101 (Williams et al, 1991). We observed that only AREB6CZ, not AREBGNZ, binds to the element in gel mobility shift assays (data not shown).…”
Section: F 1 1 : T a T C A T G A C C C C A C C C A C G A T A A G A T mentioning
confidence: 99%
See 1 more Smart Citation
“…A negative regulatory element seems important for repression of IL-2 gene transcription (61), and expression of this inhibitory factor in unstimulated Jurkat T cells may explain the lack of NFATc activity on the intact IL-2 gene promoter (Fig. 5).…”
Section: Egr-1 Regulates Il-2 Transcriptionmentioning
confidence: 99%
“…For the assay of AP-1 activity, nuclear protein extract (10 pg) was incubated with 1.5 pg poly(d1-dC) in 12 mM Hepes pH 7.9, 60 mM KCI and 12% glycerol for 15 rnin at room temperature (Williams et al, 1991). After addition of "P-labelled AP-1 binding oligonucleotide (10" cpm), the mixture was incubated for 15 min at room temperature and was then loaded on a native 6% polyacrylamide gel (acrylamide/bisacrylamide 49 : 1) containing 40 mM Tris, 226 mM glycine pH 8.2 (Caceres et al, 1991).…”
Section: Electrophoretic Mobility Shift Assaymentioning
confidence: 99%